Effects of extreme habitat loss on a local population of Reed Warblers Acrocephalus scirpaceus. Issue 2 (3rd July 2019) - Haran, Ron; Shachal, Roni; Izhaki, Ido
ABSTRACT: Total habitat loss might lead to local extinction of populations, whereas habitat loss that is extreme but partial leaves some chance for their survival. Einot Gibton, a small nature reserve in Israel, has gone through a major structural change, involving the uprooting of much of its reedbed. In an attempt to maintain the local breeding population of Reed Warblers Acrocephalus scirpaceus in the reserve, conservationists retained 10% of the original 7.55 ha of reedbed habitat in the outskirts of the reserve. The Reed Warbler population was monitored in the year before and in the three years following the structural change, to investigate how a local bird population adapts to extreme reduction of its breeding habitat. Management operations occurred mainly while the Reed Warblers were wintering in Africa. After returning in spring their density in the remnant fragments of reedbed was six times higher than before the structural changes. Despite a 47% decline in their breeding success in the first breeding season after the work, site fidelity remained high. The 75% recovery of their habitat three years after its destruction was accompanied by recovery of their breeding success. Faced with planned, accidental or natural loss of habitat, conservationists should try to ensure that parts of the habitat persist, to maintain local populations.